Improving the response of primary care providers to rural First Nation women who experience intimate partner violence: a qualitative study - Kristin Rizkalla; Marion Maar; Roger Pilon; Lorrilee McGregor; Maurianne Reade (BMC, 2020)
Abstract Background Some legacies of colonialism are that Indigenous women living in Canada experience higher rates of intimate partner violence (IPV) and that violence is often more severe relative to non-Indigenous women. This results in avoidable physical, psychological, emotional, financial, sexual and spiritual harm in the lives of Indigenous women, families, and communities. Trusted primary care providers are well positioned to provide brief interventions and referrals to treatment and services, but little is known about the providers' preparedness to support Indigenous women. Information on what enables or prevents providers to respond to Indigenous patients who experience IPV is needed in order to ensure this potential lifeline for support is realized. Methods The purpose of this community-based participatory study was to elucidate the barriers and facilitators to care for rural Indigenous women who experience IPV from the perspectives of primary care providers and to recommend strategies to improve their preparedness. Using a Grounded Theory approach, we conducted qualitative research with 31 providers to discuss their experiences with patients affected by IPV. Results The results showed providers often feel a degree of unpreparedness to deal with IPV in a clinical setting. Underlying the feelings of unpreparedness were: Recognition of patients' under disclosure of IPV due to stigma, shame and fear Lack of formal provider training on appropriate approaches to IPV Lack of referral network due to fragmented, scarce services for IPV Lack of understanding of jurisdictional complexity of First Nations and non-First Nations specific services for IPV Uncertainty how to negotiate cultural safety around IPV Multiple-role relationship & confidentiality dilemmas characteristic of small communities Risk of jeopardizing patient-provider relationship Conclusions Our recommendations to improve provider preparedness to address IPV include reducing the stigma of IPV; creating effective referral pathways; improving cultural safety within the referral network; developing services for perpetrators; engaging natural helpers in the community, and; developing policies, procedures and continuing education related to patients who experience IPV in the clinical and community setting. We suggest that increasing providers' comfort to respond to IPV for rural and Indigenous women will ultimately lead to improved safety and health outcomes.